The Rare Presence of Post-tracheotomy Tracheal Narrowing During Total Laryngectomy: A Case Report - Abbasi, Rohollah; Rezaei, Mahmoud (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Tracheotomy is a common procedure, which can induce late and serious complications, such as tracheoarterial fistulae and tracheal stenosis. The tracheal narrowing may occur due to the wrong technique at the time of tracheotomy. In this case report, we aimed to present a rare post-tracheotomy tracheal narrowing during total laryngectomy. Case presentation: The patient was a 62-year-old man with a history of smoking and 6-month hoarseness. At the time of the first surgery, direct laryngoscopy had revealed a large exophytic ulcerative mass of epiglottis and pre-epiglottic space with an extra-laryngeal extension. During laryngectomy and after the removal of the larynx, an abnormal coronal thick membrane was found in the caudal part of the specimen with significant tracheal narrowing. Discussion: There are different types of incisions that can be made for tracheotomy tube insertion, such as horizontal, vertical, T-shaped, and H-shaped incisions, as well as resection of a small section of the tracheal ring to create a window. Each type has its own advantages and disadvantages. Conclusion: Although it seems that the tracheal narrowing was due to the inverted portion of the tracheal flap during the previous tracheotomy, which was an accidental finding, however, it necessitates a proper evaluation of the tracheal incision types for tracheotomy.